2018
DOI: 10.1126/sciadv.aap7427
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium electron and lattice dynamics of strongly correlated Bi 2 Sr 2 CaCu 2 O 8+δ single crystals

Abstract: Both electron and lattice dynamics are directly observed in the nonequilibrium state of strongly correlated Bi-2212.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…One possibility is to employ time-resolved inelastic electron scattering, which provides momentum-resolved information on phonon dynamics [71][72][73]. For example, a recent study employed MeV UED to follow the energy transport between electronic to phononic systems by comparing the temporal evolution of reflection peaks and the thermal diffuse background, allowing the dynamic population of specific sub-sets of phonons to be experimentally determined [74]. In the case of In/Si(111) we observe clear evidence for a non-thermal phonon population that could in principle be quantified by combining the results of trARPES with ultrafast elastic and inelastic electron scattering.…”
Section: Momentum-resolved Population Dynamicsmentioning
confidence: 99%
“…One possibility is to employ time-resolved inelastic electron scattering, which provides momentum-resolved information on phonon dynamics [71][72][73]. For example, a recent study employed MeV UED to follow the energy transport between electronic to phononic systems by comparing the temporal evolution of reflection peaks and the thermal diffuse background, allowing the dynamic population of specific sub-sets of phonons to be experimentally determined [74]. In the case of In/Si(111) we observe clear evidence for a non-thermal phonon population that could in principle be quantified by combining the results of trARPES with ultrafast elastic and inelastic electron scattering.…”
Section: Momentum-resolved Population Dynamicsmentioning
confidence: 99%
“…The two-temperature model (2TM) [13], commonly used for metals, assumes that the electronic and phononic subsystems are each in separate equilibrium at all times and reach global equilibrium by exchanging heat [13,14]. Recent experiments have revealed that these assumptions are no longer tenable on ultrashort timescales [15][16][17][18][19]. The excited electron system reaches rapidly a uniform electron temperature through fast electron-electron scattering within a few hundred femtoseconds [20,21].…”
mentioning
confidence: 99%
“…Relativistic FED was found to be of great importance to XFELs since the generation of high-quality low emittance electron beams are beneficial to both technologies. University-based pioneering MeV FED setups have been developed at UCLA [184,207] and Osaka, [187,247] and later launched at BNL, [192] SLAC [171][172][173][193][194][195][196] and DESY [248,249]. The amount of existing knowhow in accelerator centers has been critical to obtain stable RF-photoinjectors with minimal laser-RF timing noise to reach ≈ 100 fs (rms) temporal resolution [250].…”
Section: Ultrabright Relativistic Fed Setups: Rf-photoinjectorsmentioning
confidence: 99%
“…Since the very first stroboscopic experiments utilizing electron pulses as structural probes in time-resolved diffraction experiments in the 1980s, [164,165], there has been a continuous progress in the development of brighter and faster electron diffractometers. This advancement has occurred alongside several breakthrough ultrafast electron diffraction (UED) discoveries in the gas phase, [166][167][168][169][170][171][172][173] and in solid crystalline materials measured in reflection [174][175][176][177][178] and transmission [41,[179][180][181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196] geometries. Great progress has been achieved in terms of FED (or UED) technology, with three main types of approaches being widely implemented in our research community (ordered in increasing design complexity and cost): (i) Compact (direct current, DC) FED designs, (ii) Hybrid (DC-RF) FED setups (i.e., with electron pulse rebunching) and (iii) Relativistic (RF) FED instruments.…”
Section: Introduction To Femtosecond Electron Diffraction (Fed)mentioning
confidence: 99%